Prognostic Value of Serum Osteoprotegerin Level in Patients With Hepatocellular Carcinoma Following Surgical Resection - Zhang, Chihao; Lin, Jiayun; Ni, Xiaochun; Li, Hongjie; Zheng, Lei; Zhao, Zhifeng; Qi, Xiaoliang; Huo, Haizhong; Lou, Xiaolou; Fan, Qiang; Luo, Meng (Frontiers in Oncology, 2021)
Background Multiple studies have reported that tissue or serum osteoprotegerin (OPG) level is a prognostic factor for patients with cancer. However, little is known about the role of serum OPG in hepatocellular carcinoma (HCC). In this study, we aimed to investigate whether serum OPG concentration has an effect on HCC patients’ prognosis. Methods A total of 386 eligible HCC patients undergoing radical hepatectomy were enrolled from Shanghai Ninth People’s Hospital and Zhongshan Hospital between 2010 and 2018. Kaplan-Meier curves, Cox regression model, and the restricted mean survival time (RMST) were used to estimate the association of OPG and HCC patients’ survival outcome. In addition, sensitivity analyses were carried out including subgroup analysis and propensity score matching (PSM). Results Patients were separated into two groups according to the cut-off value of OPG calculated by X-tile. Multivariate Cox analysis showed that patients with high OPG level had worse overall survival (OS) (HR: 1.93; 95% CI: 1.40–2.66, p<0.001) and disease-free survival (DFS) (HR: 1.85; 95% CI: 1.39–2.47, p<0.001) before matching. On average, RMST ratio between high and low OPG turned out to be 0.797 (95% CI: 0.716–0.887, p<0.001). In the matched population, we found that OPG level was negatively associated with OS (HR: 1.85; 95% CI: 1.25–2.74, p=0.002) and DFS (HR: 1.71; 95% CI: 1.20–2.44, p=0.003). In addition, a similar trend was further confirmed by subgroup analyses. Conclusion In a word, HCC patients with high OPG level had poorer survival rates compared with HCC patients with low OPG level. This factor could act as a potential prognostic predictor for HCC patients who underwent radical resection in the future.